PENGARUH LITERASI KEUANGAN DAN SIKAP KEUANGAN TERHADAP PENGELOLAAN KEUANGAN UMKM DI KECAMATAN GEROKGAK PADA MASA PANDEMI COVID-19 - Putu Agus Arta Setiawan; I Nengah Suarmanayasa (Universitas Pendidikan Ganesha, 2022)
This research aims to examine the influence of Financial Literacy and Financial Attitudes on Financial Management. This study is a causal quantitative study. The subject of this study is UMKM in Gerokgak Subdistrict. While the objects in this study are financial literacy, financial attitudes, and financial management. Sampling technique using simple random sampling technique, as well as determining the number of samples using the formula slovin, so that the required sample as many as 166 respondents. The data was collected with questionnaires, as well as analyzed with multiple linear regression analysis techniques. The results of this study showed that (1) financial literacy and financial attitudes had a significant effect on financial management, (2) financial literacy had a positive and significant effect on financial management, and (3) financial attitudes had a positive and significant effect on financial management in UMKM in Gerokgak Subdistrict.